Effect of garlic oil as lubricant additive into coconut and palm oils on the physical and tribological properties. (August 2019) - Gasni, D; Chandra, D; Putra, A A; Fajri, R
Abstract: Palm and coconut oils have used as an alternative source of biolubricant that is environment-friendly and biodegradable lubrication to replace petroleum oil. Due to the lack of physical and tribological properties of biolubricant, the addition of environmentally friendly additive can increase their lubricant properties. Effect of addition of garlic oil as an additive in coconut and palm oils on the physical and tribological properties was investigated and discussed. Oil treatment (OT) was used as a comparison which is known as conventional additive contained ZDDP. The results obtained from physical tribological test showed that the addition of garlic oil into coconut and palm oils had changed physical properties of these oils. Pin on disc test and ball bearing wear apparatus were conducted to study tribological properties of lubricant additives into coconut and palm oils. The addition with 5 wt % of garlic oil into palm oil showed significant improvement in both wear and coefficient of friction. The lubricant was worked very well on mixed lubrication regime stated by the smooth surface texture of inner race of bearings. Even though the results were not as good as OT; garlic oil could be an alternative as an environment-friendly additive.